Sensory profile analysis of Sumbawa ruminants milk using quantitative descriptive analysis and check-all-that-apply methods - Sari, Ratna Nurmalita; Lalu Heri Rizaldi; Ariskanopitasari; Siti Nurjanah (jurnal1, 2025)
West Nusa Tenggara, particularly Sumbawa had suitable condition for livestock production, including cow, buffalo, equine, and goat. Those ruminants produce milk that contains notable nutrients for human body. This research aimed to use Quantitative Descriptive Analysis (QDA) and Check All That Apply (CATA) method by using trained and consumer panelist, consecutively. Ten trained panelists were obtained after prior selection process and training.  Based on QDA result, bovine milk had yellowish color, salty and bitter taste. Sumbawa buffalo milk associated with thickness and creaminess. Meanwhile, equine milk appearance was white with rancid aroma and taste. Goat milk dominated with barny taste and aroma. Symmetrical plot in CATA result showed the different sensory profile among different Sumbawa ruminants milk